Exploring C for Microcontrollers A Hands on Approach - Parab, Jivan S.; Shelake, Vinod G.; Kamat, Rajanish K.; Naik, Gourish M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
The market is flooded with numbers of good books on Embedded Systems designed especially with the most popular MCS51 family. These books are traditional in nature i.e. they start with the routine architectural features of 8051, description of registers, ports, interrupts etc. Most of these things are already covered in the device data sheet and application notes. In this book all such routine things are skipped. The focus is on programming microcontrollers, to be specific MCS-51 family in 'C' using Keil IDE. Exploring C for Microcontrollers presents seventeen live case studies apart from the many basic programs organized around every on-chip resource like port, time/counter, interrupt , serial I/O etc. Rather than introducing the underpinning theory or reproducing lengthy data sheets, our approach is "learning-through-doing" and one that appeals to busy electronics designers. The 'C' codes given are well supported by easy to understand comments wherever required. Mastering the basic modules and hands on working with the projects will enable to grasp the basic building blocks for most 8051 programs. Whether you are a student using the MCS-51 family of microcontrollers for your project work or an embedded systems programmer, this is a book that will give you a kick-start in using and understanding the most popular microcontroller. Authors through their interaction with the undergraduate, postgraduate students as well as industry professionals have found that such a book is a need of the microcontroller community interested in C programming. The book will bridge the gap between the microcontroller hardware experts and the C programmers.
Microcontrollers: Yesterday, Today, and Tomorrow -- Integrated Development Environment -- Art of C Programming for Microcontrollers -- Exploring the Capabilities of On-Chip Resources Programming for I/O Ports, Interrupts and Timer/Counter -- Hyperterminal-Based Control -- Embedding Microcontroller in Routine Applications -- Microcontroller-based Measurement and Control Applications -- Securing Your Embedded System Application.
Keywords: ENGINEERING; COMPUTER SCIENCE; ELECTRONICS; SYSTEMS ENGINEERING; ENGINEERING; CIRCUITS AND SYSTEMS; ELECTRONICS AND MICROELECTRONICS, INSTRUMENTATION; PROGRAMMING LANGUAGES, COMPILERS, INTERPRETERS